EP1299 Laparoscopic – laterally extended pelvic resection. (1st November 2019) - Di Donna, MC; Cicero, C; Sozzi, G; Chiantera, V
Abstract : Introduction/Background: Lateral isolated gynecological cancer infiltrating the pelvic side wall (PSW) has been considered as a not operable surgery with poor oncological outcome. The development of the laterally extended endopelvic resection (LEER) and surgical progress for disease overcoming the endopelvic fascia infiltrating muscles and nerves, have achieved the possibility to treat those patients with a curative intent. We describe for the first time the feasibility of laparoscopic laterally extended pelvic resection (L-LEPR), with complete removal of disease. Methodology: LEPR was defined as an en bloc lateral resection of a pelvic tumor involving sidewall muscle, and/or bone, and/or major nerve, and/or major vascular structure. We performed the first L-LEPR and a subsequent vascular by-pass for an ovarian cancer recurrence. Results: A 71 year-old patient, with significant swollen right leg, affected by isolated ovarian cancer recurrence with involvement, on the PET/CT, of the right external iliac vessels and ileo-psoas muscle. L-LEPR was performed with external iliac artery decompression and right obturator, genito-femoral nerve and external iliac vein resection. A vascular bypass with bovine patch reconstruction was performed. A complete removal of recurrence was obtained (R0). Estimated blood loss was 700 mL and operative time was 385 min. No intraoperative complications were observed and the hospital stay was 11 days. Histology confirmed the isolated nodal relapse with infiltration of the surrounding tissue and in the sano margins. After 30 days, an improvement in the swelling of the leg was observed despite a deficiency in adduction and an obturator neuropathy. A re-evaluation at 6 months showed an absence of recurrence. Conclusion: We describe for the first time L-LEPR with a vascular bypass. Never before this technique was performed by laparoscopy. Our single experience shows that in highly selected cases and in referral centre, L-LEPR can be safely offered with excellent results in terms of morbidity and oncological outcome. Disclosure: Nothing to disclose